2003
DOI: 10.1191/0269216303pm793oa
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of non-albicans yeasts and detection of anti-fungal resistance in the oral flora of patients with advanced cancer

Abstract: Oral fungal infections frequently develop in individuals with advanced cancer. This study examined the oral mycological flora of 207 patients receiving palliative care for advanced malignant disease. Demographic details and a clinical history were documented from each participant. A tongue swab was collected and cultured on CHROMAgar Candida (CHROMAgar Paris, France). All yeasts were identified by germ tube test, API ID 32C profiles and, for Candida dubliniensis, by species-specific PCR. Susceptibility to fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 21 publications
8
72
3
Order By: Relevance
“…Our findings were consistent with that noted by other investigators [15][16]. Bagg et al [17] showed that patients with advanced cancer have demonstrated a high incidence (51%) of oral colonization with non-C. albicans yeasts [18]. Antifungal drug resistance of Candida spp continues to increase in response to the widespread of application of antifungal agents in treatment of cancer patients.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings were consistent with that noted by other investigators [15][16]. Bagg et al [17] showed that patients with advanced cancer have demonstrated a high incidence (51%) of oral colonization with non-C. albicans yeasts [18]. Antifungal drug resistance of Candida spp continues to increase in response to the widespread of application of antifungal agents in treatment of cancer patients.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have reported a diverse oral mycological flora in hospice patients, with a significant proportion of non-C. albicans yeasts (Sweeney et al, 1998;Jobbins et al, 1992b), a result confirmed in a recent study of oral yeast carriage among 120 patients with advanced cancer (Davies et al, 2002). In a recently completed multi-centre study (Bagg et al, 2003), the oral mycological flora of 207 patients receiving palliative care for advanced malignant disease was examined. In total, 194 yeasts were isolated, of which 95 (49 %) were C. albicans.…”
Section: Introductionmentioning
confidence: 58%
“…Yeast isolates were available from the mouths of 199 patients who were receiving palliative care for advanced cancer. These isolates had been collected and characterized during two previous studies of fungal carriage among randomly selected patients receiving palliative care in the UK (Bagg et al, 2003;Davies et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Best examples for this situation are methicillin resistant Staphylocooccus aureus (MRSA), C. difficile, candida species and vancomycin-resistant enterococcus which are the most frequent nosocomial pathogens of infection. [9][10][11] In addition undiscovered colonized patients are like a reservoir in the hospital and they easily contaminate the other patients. The two most important factors increasing the colonization rate are the duration of hospitalization and the severity of disease.…”
Section: Introductionmentioning
confidence: 99%